Sumber Daya Manusia, Sistem Pengendalian Intern, Standar Akuntansi Pemerintahan dan Kualitas Laporan Keuangan - Anita Mega Lestari; Amilin Amilin (Magister Akuntansi Universitas Pancasila, 2016)
A B S T R A C T This research aims to know influence of the human resource, internal control system and government accounting standard against the quality of financial report Information of the Ministry of National Education. Research is using survey methods. Respondents are budget planner, budget manager, financial report maker and internal control unit at the Ministry of National Education as many as 779 people, with sample 88 respondent. hypotheses testing use multiple linear regression. The result is human resources has positive and significant effect towards the quality of financial report, internal control system has positive but not significant effect toward the quality of financial report, government accounting standard has positive and significant effect toward the quality of financial report, of the Ministry of National Education. This also shows that there are synergies between human resources, internal control system, and government accounting standard to achieve the expected quality of financial report information of the Ministry of National Education. A B S T R A K Penelitian ini bertujuan untuk mengetahui pengaruh sumber daya manusia, sistem pengendalian internal dan standar akuntansi pemerintah terhadap kualitas Informasi laporan keuangan Kementerian Pendidikan Nasional. Penelitian ini menggunakan metode survei. Responden anggaran perencana, manajer anggaran, pembuat laporan keuangan dan unit kontrol internal Kementerian Pendidikan Nasional sebanyak 88 sampel pengujian responden. Pengujian hipotesis menggunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa sumber daya manusia memiliki pengaruh positif terhadap kualitas laporan keuangan, sistem pengendalian intern berpengaruh positif tetapi tidak signifikan terhadap kualitas laporan keuangan, standar akuntansi pemerintahan berpengaruh positif dan signifikan terhadap kualitas laporan keuangan di Departemen Pendidikan Nasional. Hasil penelitian juga menunjukkan adanya sinergi antara sumber daya manusia, sistem pengendalian internal, dan standar akuntansi pemerintah untuk mencapai kualitas yang diharapkan dari laporan informasi keuangan dari Departemen Pendidikan Nasional. JEL Classification: H53